Improving Post-Injury Care: Key Family Caregiver Perspectives of Critical Illness After Injury. (6th May 2022) - Ross Perfetti, Angela; Jacoby, Sara F.; Buddai, Sruthi; Kaplan, Lewis J.; Lane-Fall, Meghan
Abstract : BACKGROUND: There is little research about how caregiver experiences evolve from ICU admission to patient recovery, especially among caregivers for patients who have traumatic injuries. In this study, we characterize diverse caregiver experiences during and after ICU admission for injury. METHODS: This prospective observational study is based in a level 1 trauma center in Philadelphia, Pennsylvania. Longitudinal interviews among caregivers of patients who required ICU admission for traumatic injury were conducted from the time of ICU admission to 12 months after hospital discharge. Transcripts were analyzed using a qualitative descriptive approach. RESULTS: Sixty-five interviews were conducted with 19 caregivers. The interview results converged on four areas: experiences in the ICU, the aftermath of violent traumatic injury, caregiver responsibilities, and care in the context of the wider family. In the ICU, caregivers contended with worry and uncertainty, and they often hid these feelings. Many felt that they always needed to be at the bedside, leading to stress and exhaustion. Caregivers had difficulty communicating with their loved ones, and communication itself sometimes became a source of conflict. Over time, caregivers were burdened by many managerial responsibilities. In addition, violent traumatic injury caused an overlay of concern for patients' safety. The need to plan for recovery caused caregivers to make substantial sacrifices. As a result of these difficult experiences, some caregivers and patients drew closer together, while others were divided by conflict. CONCLUSIONS: Illness after traumatic injury may be devastating for caregivers, disrupting emotional wellbeing and other aspects of life. Caregivers are variably prepared for the challenges of ICU care and caregiving through convalescence and require robust support during and after ICU admission to enable effective communication, resource access, and an ongoing relationship with the healthcare team.